1976
DOI: 10.1002/pssa.2210370241
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer studies on the FeTe system

Abstract: Binary compounds FeTex have been prepared with x possessing the values 0.95, 1.2, and 2.0. They crystallise in the tetragonal α, hexagonal δ, and orthorhombic β phases, respectively. Mössbauer spectra are recorded for the three compositions from liquid nitrogen temperature to about 700 K. At room temperature and below, all of them exhibit quadrupole split spectra, and are characteristic of high spin Fe2+ covalently bound to the tellurium atom. At about 420 K, the spectrum of FeTe0.95 collapses into a single li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…It is worthy to note that even a small amount of excess iron atoms leads to modification of the electronic properties of the Fe‐Te layers in Fe 1.05 Te. Moreover, we have shown that differentiation of the iron atoms into four groups is a reason for the asymmetry of the Mössbauer spectra for powdered samples of Fe(Se1xTe x ) compounds, reported in previous papers . We presume that our results could be extended on the entire class of Fe1+ySe1xTe x compounds which contain excess iron atoms.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…It is worthy to note that even a small amount of excess iron atoms leads to modification of the electronic properties of the Fe‐Te layers in Fe 1.05 Te. Moreover, we have shown that differentiation of the iron atoms into four groups is a reason for the asymmetry of the Mössbauer spectra for powdered samples of Fe(Se1xTe x ) compounds, reported in previous papers . We presume that our results could be extended on the entire class of Fe1+ySe1xTe x compounds which contain excess iron atoms.…”
Section: Resultssupporting
confidence: 73%
“…Observation of the fine structure of the Mössbauer spectra complemented by ab initio calculations of the electric field gradients (EFG) on iron nuclei allows establishing a statistical distribution of excess iron atoms over the FeTe lattice. We argue that unexpected asymmetry of Mössbauer spectra reported in numerous papers for powdered samples can be attributed to over‐stoichiometric iron atoms and their influence on the regular iron atoms in the Fe1+y(Se1xTe x ) type compounds.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Probably, there is a certain amount of FeS hidden inside the FeTe structure invisible in the XRD characterization. FeTe 2 is paramagnetic down to 77 K [4,5]. It has an internal field which is less than 30 T. The magnetic component C 2 may be attributed to FeTe or FeTe 1Àx S x with low sulphur content.…”
Section: Resultsmentioning
confidence: 96%
“…The FeTe x system with different values of x has been studied a lot [4]. It exhibits various structures depending on the Fe-Te ratio [4][5][6]. An iron excess causes structural transformation.…”
Section: Introductionmentioning
confidence: 99%